A new species of Eurysthea Thomson, 1861 (Coleoptera: Cerambycidae) from Colombia - Taboada-Verona, Carlos; Botero, Juan Pablo (Zootaxa, 2018)
Eurysthea Thomson, 1861 is currently composed of 23 species (Botero & Santos-Silva 2017; Monné 2018). Its distribution extends from Nicaragua to Argentina, with a certain preference toward the sub-Andean forest areas and the Atlantic forest (Martins 2005; Monné 2018). Currently, six species are recorded for Colombia (Botero & Santos-Silva 2017; Monné 2018): E. antonkozlovi Botero & Santos-Silva, 2017; E. barsevskisi Botero & Santos-Silva, 2017; E. cribripennis Bates, 1885; E. rotundicollis (Martins, 1995); E. sordida (Erichson, 1847); and E. tatianakozlovae Botero & Santos-Silva, 2017.